Museums and the construction of race ideologies: the case of natural history and ethnographic museums in South Africa - Kasibe, Wandile Goozen (University of Cape Town, 2020)
This enquiry investigates the entanglement of the Natural History and Ethnographic museums in the construction of racist ideologies, the perpetuation of colonial reasoning and its continuities in South Africa today. It draws our attention to the fact that the museological institution was complicit and colluded in the perpetuation of colonial "crimes against humanity", thereby rendering its own institutionality a colonial "crime scene" that requires rigorous "de-colonial" investigation in the "post-colonial" era. In the attempt to shed more light into the miasma caused by colonial and apartheid rule, I turn to the practices of 'scientific enquiry' and public exhibitions to advance an argument that these museum exhibits were a precursor to genocide. The study further argues that, these public exhibits of Africans were instrumental in popularizing theories of racial ideology and white 'supremacy', dehumanizing Africans and thereby creating public justification for colonial dispossession of Africans. To support my argument I discuss the underpining politics that informed the making and dismantling of the South African Museum's "Bushman" diorama. Further to the discussion about dioramas, human zoos and other forms of racializing spectacles, I make reference to the haunting narratives of the African Diasporas to provide context and perspective. These African individuals are: Sarah Baartman ('The Hottentot Venus') and El Negro 'object 1004' and then Ota Benga, the "Congolese Pygmy", who was displayed with an orangutan at the Bronx Zoo in America in 1906, and labelled "the Missing Link". Part of my attempt to understand the story of Benga, I set on a journey to track him to the United States (US). To point out and expose these human wrongs I incorporate and discuss images of decapitated heads, prepared skulls and images of emaciated Africans, not to reproduce colonial traumas, but to unveil the gravity of the violence that was emitted against those who were deemed 'lesser' beings, namely the black Africans and KhoiSan in particular. The colonial museum collected these human remains for race 'science' under politically motivated circumstances to feed to the idea that black 'inferiority' and white 'superiority' as a new global socio-political order. The evidence of diverse materials (photographs, manuscript letters etc) that I have used here point to the toxic collusion between the colonial administration and the museological institution in the perpetuation of racial violence in South Africa. The contribution among many other contributions of this study is the interrogation of these colonial traces in the museological institution and the proposal of a decolonial project framed in the form of a Museum Truth, Repatriation and Restitution Commission (#MuseumTRRC). The MuseumTRRC as both a socio-political and museological tool sharply invokes the interplay between the construction of race and the establishment of the colonial museum in a way that helps us understand how the museological institution influenced laws of racial separation that South Africa's apartheid past was built on. The MuseumTRRC is presented as the sine qua non in the framing of the 'new museum' of the future. In a nutshell, the study presents to us new ways of seeing museums and their sociological impact of their collections on people's lives today. It presents what I term in this thesis as 'museumorphosis', a process of radical epistemological shift that should take place in the museum in order for the museological institution to effectively respond to the sensibilities of the 21st Century and beyond.